ANALIZA STRUKTURE STAVOVA I MI ŠLJENJA NASTAVNIKA RAZREDNE NASTAVE PREMA FIZIČKOM VASPITANJU - Enver Međedović; Ahmet Međedović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
and ac ti vity in so cial or ga ni za ti ons for physi cal cul tu re, en ga ged pe da go gu es physi cal cul tu res in pe da go gic ac ti vity, analyses and for ti fi ca tion re spon si bi lity in work sport union com mu nity, par ti ci pa tion school on con test in fra me school union for sport and olympic edu ca tion, en ga ge ment on re se arch pro ject, opi nion abo ut or ga ni za tion work physi cal edu ca tion from I to IV gra des pri mary school, sum pos si bi lity for advance ment physi cal edu ca tion thro ugh co o pe ra tion with pe da go gic of fi ce, in fl u en ce school equ ip ment te ac her on qu a lity of work. On pat tern of 60 te ac hers physi cal edu ca tion, pe da go gu es physi cal edu ca tion which work in pri mary and high school on re gion com mu nity No vi Pa zar a way qu e sti on mark are at ta i ned re sults which are il lu stra ting ta bu lar, grap hic, de scrip ti ve met hod.